Expanding tryptophan-containing cyclodipeptide synthase spectrum by identification of nine members from Streptomyces strains - Liu, Jing; Yu, Huili; Li, Shu-Ming (Applied microbiology and biotechnology, 2018)
Cyclodipeptide synthases (CDPSs) comprise normally 200–300 amino acid residues and are mainly found in bacteria. They hijack aminoacyl-tRNAs from the ribosomal machinery for cyclodipeptide formation. In this study, nine new CDPS genes from eight Streptomyces strains were cloned into pET28a vector and expressed in Escherichia coli . Structural elucidation of the isolated products led to the identification of one cyclo - l -Trp- l -Leu, two cyclo - l -Trp- l -Pro, and three cyclo - l -Trp- l -Trp synthases. Other three CDPSs produce cyclo - l -Trp- l -Ala or cyclo - l -Trp- l -Tyr as the major cyclodipeptide. Total product yields of 46 to 211 mg/L E. coli culture were obtained. Our findings represent rare examples of CDPS family derived from actinobacteria that form various tryptophan-containing cyclodipeptides. Furthermore, this study highlights the potential of the microbial machinery for tryptophan-containing cyclodipeptide biosynthesis and provides valid experimental basis for further combination of these CDPS genes with other modification genes in synthetic biology.